Copula‐function‐based analysis model and dynamic reliability of a gear transmission system considering failure correlations. Issue 1 (5th July 2018) - Wei, J.; Pan, Z.; Lin, X.; Qin, D.; Zhang, A.; Shi, L.
Abstract: In this study, an improved prediction model is introduced to assess the residual strength of gear transmission systems. The residual strength and stress‐strength interference theories are then combined to facilitate the study of the reliability of the gears and bearings in these systems. Based on the copula function, the correlation between the gear contact and bending failure is determined. The relationship between the copula function and reliability is used to determine the dynamic reliability of the gears while considering multiple correlated failure modes. In this manner, more accurate and dynamic reliability attenuation characteristics are obtained for the gear transmission system.